Effect of TPRC Using Preezi on Teaching Reading to Junior High School Students - M. Alimul Huda; Feri Huda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Reading is very important for students because their learning success is highly dependent on their reading comprehension. In order to read well, teachers must support learning with appropriate teaching methods. This study was a quantitative study to apply a quasi-experimental design to compare the TPRC strategy with Prezi and Grammar Translation Method to the first-year students in SMPN 1 Sutojayan. Studies have shown significantly higher performance than those taught using GTM. It was concluded that TPRC strategy using Prezi was effective in teaching the reading of descriptive texts for junior high school.